Advertisement as a Converter Between Reality and Fantasy: The Case of Is Bank Ads - Demirci, Kenan (Ankara Univ, Fac Communication, 2016)
In this study, media reality subject, which is seen as a result of conversion occurring in late modern communal conditions, was handled through advertisement example. The leading role of advertisement in daily life and in media was effective in the selection of this subject. In this context, the aim of the study is to discuss to what extent advertisements, which have recently made important changes in their strategies, draw the borders between reality and fantasy. In the study, various advertisements of Turkiye Is Bankasi A.S were examined in terms of their establishment of reality. In resolution of advertisement movies, semiotic analysis method was used and in the resolution, especially the triple definition related with the indicators developed by Pierce was focused on. In this definition the indicators are separated into three as iconic, indexical and symbol. As a result of the resolution, it was concluded that the borders between reality and fantasy were blurred in the examined advertisements and that this was used as an important strategy in creating the reality of the product, advertisement of which is made.
Keywords: Advertisement; Is Bankasi; Reality; Semiotics; Pierce